Network Metadata (NETTA) : Sistem Monitoring Jaringan Dan Metadata UPT BMKG Dengan Notifikasi Berbasis Telegram - Siti Zainab; Djoko H. Nugroho; Masbah R.T. Siregar; Hendi Satria WD; Abdul Multi; Muhammad Nur Huda (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT BMKG has a role to disseminate geo-hydrometeorological information in the fields of Meteorology, Climatology and Geophysics. The dissemination process requires data from BMKG operational equipment spread across 183 Technical Implementation Units (UPT) throughout Indonesia. The recorded data must be collected and disseminated using a communication network. The existing network monitoring system currently at BMKG uses the PRTG monitoring application but can only be accessed by central employees. Thus, a system that can be accessed by regional employees to see the condition of the communication network in each UPT is needed, so that it can support operations. This paper discusses monitoring system and communication network metadata design with notifications using telegrams that can be adapted for operations at BMKG called NetTa (Network Metadata). The system consists of a network monitoring dashboard, provider rental metadata dashboard, network monitoring notifications via Telegram bots. The system operates in real time and can be accessed from anywhere using a smartphone and PC. The results of functional testing show that monitoring system of all existing features on the system can be accessed according to the design. Telegram notifications can provide network device status as well as warnings if there is a communication network interruption based on the monitored sensor code Keywords : Monitoring, Network, UPT BMKG, Telegram, Metadata